Eksistensi Hukum Islam dalam Sistem Perundang-Undangan Indonesia: Studi Zakat, Haji, dan KHI: The Existence of Islamic Law in the Indonesian Legislative System: A Study of Zakat, Hajj, and KHI - Kamaluddin Kamaluddin; Abd. Rahman; Rahmatiah Rahmatiah (Litera Academica Publishing, 2026)
The existence of Islamic law within the Indonesian legal system is explained through three main instruments: the Zakat Law, the Hajj Management Law, and the Compilation of Islamic Law (KHI). This study employs a library research method with a normative juridical approach, focusing on the analysis of legislation, academic literature, and previous research findings. The results highlight the significant role of Islamic law in accommodating the needs of the Muslim community through formal regulations, where the Zakat Law affirms zakat as a socio-economic obligation, the Hajj Law comprehensively regulates pilgrimage management, and the KHI serves as a reference for Islamic family law in safeguarding religious practices. Nevertheless, the implementation of these instruments is influenced by institutional frameworks, legal politics, and the pluralistic nature of Indonesian society. This study underscores the dynamic and evolving integration process of Islamic law within the national legal system.